Exploring the Students’ Perception of Home Assignments on Academic Performance at School Level Students in Nepal - Lamsal, Mani Ratna (KMC Research Journal, 2025)
Home assignments have been a controversial matter among students, parents, teachers and educational institutions in general and have raised serious concerns over the last few decades because home assignments restrict students from engagements in the out-of-class activities. Bodies of research present mixed views about the needs and effects of homework. Few reasons, why teachers and academic institutions assign homework to their students, entail; helping students to prepare for exams; develop good working habit; motivate students to learn; develop independent learning and critical thinking; and to improve and increase the writings of students. This qualitative study is conducted at few private and public secondary schools (covering classes 11 & 12) in Kathmandu, Nepal and the key intent was to explore major effects of home assignments on students. It was based on purposive sampling technique for primary data supported by Open-ended interview guidelines that helped to gather information about students’ perception and their first-hand experiences regarding the effects of homework assignments on academic performance. 50 students consisting of 25 males and 25 females were interviewed with open ended questions. The study has come up with conflicting findings across individuals regarding students’ perceptions on home assignments since the respondents in differing numbers accepted it to play a crucial role in supporting learning linking it with the key role to enhance writing skills, foster critical thinking, and promote independent learning because it serves as a valuable tool for reinforcing classroom learning from beyond the school environment engagement. On the contrary, the other side of the dual perspective entailed students’ perception that portrayed homework as merely burdensome indicating a dichotomy or critical tension in educational practices however suggesting effectiveness of homework with proper workload and work having its relevance to learning objectives.